Comparatively Evaluation of the Methods Used in the Assessment of Health and Impairment of Body Composition - Şükrü Ahmet Ayyıldız; Süleyman Yagız; Sermin Algül; Oğuz Özçelik (LookUs Bilisim A.S., 2025)
INTRODUCTION: Assessment of body composition is an important way that reveal valuable information about the health status of individuals. To evaluate the effectiveness of the methods, the body compositions of young male and female students were comparatively evaluated using the bioelectrical impedance method (BIA), body mass index (BMI), and waist-hip ratio (WHR). METHODS: A total of 226 (n= 112 males and n= 114 females) young students participated in this study. Body composition analyses were performed using BIA, BMI, and WHR. RESULTS: Considering the whole data, a statistically significant correlation between BMI and BIA was observed. However, there is a difference in risk groups with low and normal values that may result in the differences between the cut-off points determined by ethnicity and gender. DISCUSSION AND CONCLUSION: In general, although anthropometric measurements have provided meaningful results for population evaluation, technological evaluations should be taken into account in measurements in decision-making situations related to the health status of individuals.
Keywords: body composition; R; Medicine; fat mass; body mass index; waist to hip ratio; bioelectrical impedance analyses; fitness